Synthesis and mesomorphic properties of new imines and copper(II) complexes - Bilgin-Eran, B; Yörür, Ç; Uzman, S (ELSEVIER SCIENCE SA, 2002)
The synthesis and mesomorphic properties of a serie of 4-(alkyloxy)-N-(4-hexylphenyl)-2-hydroxybenzalimine (2) and their copper(H) complexes (3) are reported. The compounds were characterized by spectroscopic methods (1R, H-1-, C-13-NMR and MS). The calamitic liquid crystal series of imines (2) and copper(II) complexes (3) exhibited smectic mesophases, which were characterized by differential scanning calorimetry (DSC) analysis and optical polarizing microscopy. (C) 2002 Published by Elsevier Science B.V.
Keywords: liquid crystals; metallomesogens; Schiff bases; copper(II) complexes; LIQUID-CRYSTALS; TRANSITION-METALS; BEHAVIOR; DERIVATIVES; BASES; EPR; Chemistry